Biomaterials for Musculoskeletal Regeneration : Applications - Basu, Bikramjit; Ghosh, Sourabh (Springer Singapore : Imprint: Springer, 2017)
This book discusses a number of case studies to showcase the translation of research concepts to lab-scale materials development for biomedical applications. The book intends to motivate active researchers to develop new generation biomaterials. This book is meant for readers, who are already familiar with the broad area of biomaterials. The book introduces readers to the field of additive manufacturing of biomaterials and teaches them how to extend this innovative processing approach to a variety of biomaterials for musculoskeletal applications. It covers both in vitro and in vivo biocompatibility and toxicity assessment for a broad range of biomaterials in the context of bone tissue engineering. It works to sensitise researchers in the field of translational biomedical engineering on the importance of clinical trials and discusses the challenges ahead in this important field of research. This book will bee useful to clinicians, professionals and researchers alike.
Keywords: Materials science.; Biomedical engineering.; Regenerative medicine.; Tissue engineering.; Biomaterials.; elektronické knihy; electronic books